Beowulf - Clark, George (Twayne Publishers, 1990)
Provides in-depth analysis of the epic poem Beowulf
Includes bibliographical references and index
Keywords: Epic poetry; English (Old); Monsters in literature; Dragons in literature; Heroes in literature